Simulacra in women’s majelis taklim based on Jean Baudrillard’s perspective - Srinarwati, Dwi Retnani; Pratiwi, Pinky Saptandari Endang; Arimbi, Diah Ariani (Jurnal Studi Komunikasi, 2020)
This research aimed to discover the meaning of the Majelis Taklim for upper-middle-class worshipers and how simulacra-simulation and hyperreality processes occur in the Salafi Majelis Taklim. This research was a qualitative descriptive study which explored data through participatory observation, in-depth interviews, and documentation. The data was analysed by Miles and Huberman’s analysis through three related sub-processes, namely data reduction, data display, and conclusion drawing/verification. Jean Baudrillard’s simulation-simulacra theory was used as the primary research framework. The results of data analysis revealed that (1) Majelis Taklim became a mean of hijrah for the members. The hijrah referred here is the conversion from non-Salafi to a Salafi movement. It is an ideology that Muslims must return to the Qur'an and the Sunnah of the Apostles to become more religious, increase social piety, and stay away from restrictions (usury, photos, polytheistic acts, etc.). (2) With media’s support, Majelis Taklim became a simulacrum for the simulation process, which ultimately led to hyperreality, especially signs consumption practices (fashion, worship groups). (3) Hyperreality occurred in religious life.